Eyewitness: Volcano & Earthquake - Van Rose, Susanna (New York, New York : DK Publishing, 2022)
"Discover the Earths most explosive volcanoes and what its like to experience an earthquake feels like in this picture-led guide to the hotspots of the world This book tells you everything you need to know about the Earths most extraordinary natural forces - from active volcanoes, including Kilanea in Hawaii and Etna in Italy, to devastating earthquakes that have hit San Francisco and Japan. Discover how the eruption of Mount Vesuvius devastated the cities of Pompeii and Herculaneum, but left in its wake remarkably preserved treasures. Find out, too, how dogs can search for survivors in the aftermath of a huge quake. Eyewitness Volcano and Earthquake explores how tectonic plates collide, what causes magma to escape from deep inside Earth and why eruptions affect our weather. Learn how scientists predict and measure the magnitude of earthquakes, and find out what a volcanologist does. Packed with striking full-colour photographs and illustrations of lava flows, pyroclastic clouds, rocks and precious stones, preserved bodies and petrified objects, and much more along with amazing facts, infographics, statistics, and a timeline to reveal the most devastating volcanoes and earthquakes in history. Part of DKs best- selling Eyewitness series, which is now getting an exciting makeover, this popular title has been reinvigorated for the next generation of information- seekers, with a fresh new look, new photographs, updated information, and a new eyewitness feature - fascinating first-hand accounts from experts in the field."--Provided by publisher.
Keywords: Volcanoes -- Juvenile literature; Earthquakes -- Juvenile literature; Geology